2021
DOI: 10.1049/rpg2.12192
|View full text |Cite
|
Sign up to set email alerts
|

Rotors for wave energy conversion—Practice and possibilities

Abstract: This review studies some of the existing ideas which create a fundamentally new direction for wave energy converter (WEC) development, obtaining energy from the elliptical motion of particles in water waves using a rotor. The review focuses on three main aspects of rotor-based WECs: experimental study of the developed prototypes, derivation and development of the mathematical models, and control effectors and philosophies for the proposed devices. The range of developed small scale prototypes and their experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The reviews of cyclorotor-based WECs conducted by different authors (Scharmann 2014;Folley and Whittaker 2019;Ermakov and Ringwood 2021) have shown that a cyclorotor may have a wide range of possible actuators and may be suitable for different strategies of wave energy extraction. A significant analysis of lift-based wave energy converters and their potential was subsequently conducted by Folley and Whittaker (2019).…”
Section: Overview Of the Existing Prototypes And Control Strategiesmentioning
confidence: 99%
“…The reviews of cyclorotor-based WECs conducted by different authors (Scharmann 2014;Folley and Whittaker 2019;Ermakov and Ringwood 2021) have shown that a cyclorotor may have a wide range of possible actuators and may be suitable for different strategies of wave energy extraction. A significant analysis of lift-based wave energy converters and their potential was subsequently conducted by Folley and Whittaker (2019).…”
Section: Overview Of the Existing Prototypes And Control Strategiesmentioning
confidence: 99%
“…The cyclorotor-based WEC is simulated with the use of a bespoke mathematical model which has an integro-differential equation form (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), simulated in Python [32]. The control problem is non-convex due to the high non-linearity of the model equations.…”
Section: Mathematical Formulation Of the Optimal Control Problemmentioning
confidence: 99%
“…However, as it has been shown in [3]- [6], the performance of the cyclorotor requires real-time control (especially in panchromatic seas). The reviews of cyclorotor-based WECs [6]- [8] have identified the variation of the rotational rate and hydrofoil pitch angle as the most advanced actuators. However, the optimal control strategies, the best real-time actuators, and appropriate performance metrics, need to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…T HOUGH research into lift-based cyclorotor-based wave energy converters (WECs) began over 40 years ago, development in the interim has been sporadic and slow [1]. Much of the recent progress has been documented in the PhD thesis of Scharmann [2] and the work of Hermans [3] and Siegel [4], [5].…”
Section: Introductionmentioning
confidence: 99%